PERCEPTION AND EFFECTIVENESS OF CHATGPT AS AN ENGLISH LEARNINGASSISTANT IN THE CONTEXT OF VOCATIONAL EDUCATION - Lika Silvia Batubara (Indonesian Journal of Education (INJOE), 2025)
The rapid development of artificial intelligence (AI) has brought new opportunities to the field of education, especially in language learning. One of the most widely discussed tools is ChatGPT, an AI-based platform capable of generating human-like responses through natural language processing. This study explores how vocational students perceive the use of ChatGPT as a learning companion and examines how effective it is in supporting their English writing skills. Using a descriptive quantitative method, data were collected from 40 students in the Computer Engineering program at Politeknik Unggulan Cipta Mandiri. The results show that most students view ChatGPT as easy to use and helpful, particularly in improving sentence structure, enriching vocabulary, and correcting grammar. While the tool was generally well-received, some students still faced difficulties in crafting prompts that lead to accurate responses. These findings suggest that, with proper guidance and ethical training, ChatGPT can be meaningfully integrated into vocational English learning to enhance student engagement and writing performance.